Into God's presence: Prayer in the New Testament - Longenecker, Richard N.; (1930-2021) (U.S.A., 2001)
The Christian life cannot be fully understood or experienced without first grasping the importance of prayer. Yet prayer, as it is found in the Christian scriptures, has received limited attention as a topic of study. Into God's Presence explores the nature and use of prayer throughout the entire New Testament. Written by twelve leading biblical scholars with diverse confessional perspectives, this insightful volume first discusses Christian prayer in relation to prayer in the Old Testament, the Greco-Roman world, first-century Judaism, and the Dead Sea Scrolls. The rest of the book takes an instructive look at prayer as it appears from Matthew to Revelation, with special attention given to Jesus as an exemplar and teacher of prayer.
Keywords: Prayers